2014
DOI: 10.3109/13880209.2013.877491
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxysafflor yellow A suppresses liver fibrosis induced by carbon tetrachloride with high-fat diet by regulating PPAR-γ/p38 MAPK signaling

Abstract: Context: One approach to protect against liver fibrosis is the use of herb-derived natural compounds, such as hydroxysafflor yellow A (HSYA). The antifibrosis effect of HYSA against liver fibrosis has been investigated; however, its mechanisms have not yet been entirely revealed. Objectives: To study the protective effects of HSYA on liver fibrosis induced by carbon tetrachloride (CCl 4 ) and a high-fat diet (HFD), and to determine the mechanism of action of HSYA. Materials and methods: CCl 4 and HFD were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…In the current investigation, immunohistochemical reactivity of both PPAR-α and PPAR-γ, increased in omega-3 supplemented rats compared to the only CCl 4 injected animals. Therefore, our results correlate the findings of previous studies [42,65,66] indicating CCl 4 treatment prominently reduce the expression of PPAR-γ, and that omega-3 supplementation has beneficial effects in reducing the development of degenerative changes induced by CCl 4 .…”
Section: Discussionsupporting
confidence: 81%
“…In the current investigation, immunohistochemical reactivity of both PPAR-α and PPAR-γ, increased in omega-3 supplemented rats compared to the only CCl 4 injected animals. Therefore, our results correlate the findings of previous studies [42,65,66] indicating CCl 4 treatment prominently reduce the expression of PPAR-γ, and that omega-3 supplementation has beneficial effects in reducing the development of degenerative changes induced by CCl 4 .…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have reported that HSYA is a potential antifibrotic agent. HSYA can inhibit hepatic stellate cell (HSC) activation and prevent the progression of CCl 4 and oxidation stress‐induced liver fibrosis in vivo . Our preliminary studies also showed that HSYA could attenuate pulmonary fibrosis induced by bleomycin (BLM) and decrease the mRNA expression of TGF‐β1 in the lungs of pulmonary fibrotic mice …”
Section: Introductionmentioning
confidence: 61%
“…showed that HSYA inhibited proliferation and migration of vascular smooth muscle cells induced by PDGF‐BB through mediating Akt signalling. Liu et al . showed that HSYA inhibited liver fibrosis via p38 MAPK signalling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hu et al (2016) showed that HSYA had a protective effect against fibrosis in renal cells through inhibiting the TGF-β1/Smad3-mediated epithelial–mesenchymal transition signaling pathway, while Zhang et al (2011) found that HSYA markedly attenuated the development of liver fibrosis by directly blocking TGF-β1-regulated hepatic stellate cell activation. Liu et al confirmed that peroxisome proliferator-activated receptor-γ and p38 MAPK signaling played pivotal roles in the prevention of liver fibrosis induced by carbon tetrachloride and a high-fat diet (Liu et al, 2014). Jin et al (2016) recently showed that HSYA attenuated BLM-induced pulmonary fibrosis in mice.…”
Section: Discussionmentioning
confidence: 99%